2007
DOI: 10.1021/ic062362z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Ligand Substitution at the Nickel(II) Sites of Cubane-Type and Cubanoid NiFe3S4 Clusters Relevant to the C-Clusters of Carbon Monoxide Dehydrogenase

Abstract: Substitution reactions at the nickel site of the cubane-type cluster [(Ph3P)NiFe3S4(LS3)]2- (2) have been investigated in the course of a synthetic approach to the C-clusters of CODH. Reaction of 2 with RS- or toluene-3,4-dithiolate affords [(RS)NiFe3S4(LS3)]3- (R = Et (5), H (6)) or [(tdt)NiFe3S4(LS3)]3- (7), demonstrating that anionic sulfur ligands can be bound at the NiII site. Clusters 5 and 6 contain tetrahedral Ni(micro3-S)3(SR) sites. Cluster 7 is of particular interest because it includes a cubanoid N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 46 publications
0
41
0
2
Order By: Relevance
“…If CO 2 (and its mimics) indeed bind to the S = 1 = 2 C red1 state, it should be possible to probe that binding further by searching for 13 C hyperfine interactions by using ENDOR or ESEEM spectroscopy. The electronic structure of C red2 remains poorly understood, and future efforts should be placed at preparing site-directed mutants in which the B-cluster is either absent or not reducible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If CO 2 (and its mimics) indeed bind to the S = 1 = 2 C red1 state, it should be possible to probe that binding further by searching for 13 C hyperfine interactions by using ENDOR or ESEEM spectroscopy. The electronic structure of C red2 remains poorly understood, and future efforts should be placed at preparing site-directed mutants in which the B-cluster is either absent or not reducible.…”
Section: Methodsmentioning
confidence: 99%
“…[15] related synthetic clusters have been studied by Münck, Holm, et al, who found that such clusters can exist in states ranging from all-ferrous to all-ferric. [12,13] The electronic configuration of C red2 is uncertain because of overlap of C red2 and reduced Bcluster Mössbauer features, as well as weak magnetic interactions between C red2 and the reduced B-cluster. C red2 should be 2 electrons more reduced than C red1 , but where those electrons localize on the C-cluster is unknown.…”
mentioning
confidence: 99%
“…Further, the approximately planar Ni sites in intermediate (b) and the cyanide-ligated C-clusters (c) and (d) (Figure 1) are approached in clusters such as [(tdt)NiFe 3 S 4 (LS 3 )] 3− . This and related cubanoid clusters are produced by phosphine substitution with a strong in-plane chelating ligand and attendant rupture of the axial Ni-(µ 3 -S) bond 16,17. However, key attributes of the C-cluster have not been experimentally attained.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the anaerobic CODHs, attempts to mimic the spectroscopic properties of the NiFeS active site with synthetic complexes were underway even before the determination of the active site structure. There have been two major approaches: construction of [NiFe 3 S 4 ] clusters, spearheaded largely by the Holm group [151][152][153][154][155], and efforts to make heterobimetallic [NiFe] complexes, research closely related to the modeling of [NiFe]-hydrogenases (see Sect. 3).…”
Section: Structural Models Of Codhsmentioning
confidence: 99%